Strengthen farmers' fertilizer self-sufficiency in the tourist area with a reduce-reuse-recycle system - Reni Ustiatik; Beauty Laras Setia Pertiwi; Ayu Putri Ariska; Kurniawan Sigit Wicaksono; Sativandi Riza; Syamsu Ridzal Indra Hadi; Achmad Riyanto; Endang Arisoesilaningsih; Sri Rahayu Utami (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Mining activities at Tebing Breksi are a vital source of income for the community in Sambirejo village, Sleman Regency, Yogyakarta. However, these activities have caused several environmental issues, such as lowered pH levels, reduced soil fertility, shallow soil profiles, and water scarcity. Additionally, mining has led to biodiversity loss and land degradation, making post-mining reclamation essential to restore the area's environmental and social functions. This project aimed to enhance the community’s skills in soil analysis and the production of liquid organic fertilizer using effective methods. The activities took place in the Tebing Breksi tourist area, located in Nglengkong, Sambirejo Village, Prambanan District, Sleman Regency. The project included a Focus Group Discussion (FGD), soil fertility analysis using test kits, and the creation of liquid organic fertilizer from household waste. During the FGD, it was discovered that the local community had not received prior training on producing fertilizer from household and organic waste. Until then, they relied on expensive commercial fertilizers to quickly stabilize soil pH. Through this training, the community learned how to perform rapid soil chemical analysis and produce liquid organic fertilizer independently. As a result, they can now apply the fertilizer locally, improving soil conditions and reducing their reliance on costly commercial products.